Detection of Mycobacterium tuberculosis DNA in CD34+ peripheral blood mononuclear cells of adults with tuberculosis infection and disease - Repele, Federica; Alonzi, Tonino; Navarra, Assunta; Farroni, Chiara; Salmi, Andrea; Cuzzi, Gilda; Delogu, Giovanni; Gualano, Gina; Puro, Vincenzo; De Carli, Gabriella; Girardi, Enrico; Palmieri, Fabrizio; et al. (International journal of infectious diseases, 2024)
•Mycobacterium tuberculosis (Mtb) DNA is detected in the peripheral blood cells of donors with tuberculosis (TB) or TB infection.•Mtb DNA is detected in the peripheral blood cells of donors with presumptive TB.•Mtb DNA detection is more frequent in peripheral CD34+ cells.•CD34+ cells may represent a niche for Mtb.•Mtb DNA in peripheral blood cells may be a new microbial biomarker. To investigate whether Mycobacterium tuberculosis (Mtb) DNA is detected in peripheral blood mononuclear cells (PBMC) of subjects with tuberculosis (TB) or TB infection (TBI) living in a low-burden country. We prospectively enrolled 57 patients with TB, 41 subjects with TBI, and 39 controls in Rome, Italy. PBMC were isolated, cluster of differentiation (CD)34+ and CD34− cells were immunomagnetic separated, DNA was extracted, and digital polymerase chain reaction for IS6110 and rpoB sequences was used to detect Mtb DNA in PBMC subsets and unfractionated PBMC. We detected Mtb DNA at a low copy number in CD34+ cells in 4o f 30 (13%) patients with TB, 2 of 24 (8%) subjects with TBI, and 1 of 24 (4%) controls. Mtb DNA was detected in unfractionated PBMC in 3 of 51 (6%) patients with TB, 2 of 38 (5%) subjects with TBI, and 2 of 36 (6%) controls. In CD34− cells, only 1 of 31 (3%) subjects with TBI tested positive for Mtb DNA. Mtb DNA was detected at low frequencies and levels in the PBMC of subjects with TBI and donors with TB living in a low-burden country. In particular, Mtb DNA was detected more frequently in CD34+ cells, supporting the hypothesis that these cells may represent a Mtb niche. This finding informs biological understanding of Mtb pathogenesis and may support the development of a microbial blood biomarker for Mtb infection.